2019
DOI: 10.3390/toxins11050266
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Importance of Toxicity: Sea Anemones Maintain Toxic Defence When Bleached

Abstract: Cnidarians are amongst the most venomous animals on the planet. They are also under significant threat due to the impacts of climate change. Corals and anemones undergo climate-induced bleaching during extreme environmental conditions, where a loss of symbiotic photosynthetic algae (zooxanthellae) causes whitening in colour, loss of internal food supply, and reduction in health, which can ultimately lead to death. What has yet to be determined is whether bleaching causes a reduction in the production or qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Interestingly, the results obtained in this study agree with what was recently found by Hoepner et al , [149], who reported that the venom from the sea anemone Entacmaea quadricolor , exposed to long-term light-induced bleaching, preserve its hemolytic activity and lethality. These findings support the hypothesis that some cnidarians that have suffered bleaching are able to prey heterotrophically, giving them a better chance to resist the effects of thermal stress.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the results obtained in this study agree with what was recently found by Hoepner et al , [149], who reported that the venom from the sea anemone Entacmaea quadricolor , exposed to long-term light-induced bleaching, preserve its hemolytic activity and lethality. These findings support the hypothesis that some cnidarians that have suffered bleaching are able to prey heterotrophically, giving them a better chance to resist the effects of thermal stress.…”
Section: Discussionsupporting
confidence: 93%
“…The evidence of salinity as an influencing factor to algal toxicity is vast, so why this has not been explored further within animal toxins/venom is perplexing. Indeed, multiple studies control for salinity when analysing venom ( Dutertre et al, 2010 ; Hoepner et al, 2019 ; Sivan et al, 2010 ), presumably to mitigate its influence, yet there is very little research into its effect.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…However, comparatively, it is evident that a six‐week period was sufficient for transcription and translation processes to alter expression patterns in the nontoxin proteome of T. coccinea nematocytes, but such adaptation certainly did not extend to the venom phenotype. Venomous anthozoans often elaborate the same combination and potency of toxins for both predation and defense, potentially where constitutive expression is adequate for both purposes, even during a severe “bleaching” event causing an enhance requirement for heterotrophic metabolism (Hoepner, Abbott, & Burke da Silva, ). Changes in predator exposure, but not diet, elicit a larger venom proportion of defensive toxins than predatory toxins in the scorpion Liocheles waigiensis (Gangur et al, ), and remarkably, carnivorous cone snails are reported to switch between distinct venoms in response to predatory or defensive stimuli (Duterte et al, ).…”
Section: Discussionmentioning
confidence: 99%